Interface pressure and temperature monitoring for pressure injury prevention: integrative review (Research, Society and Development, 2022)
Introduction: Pressure injury is a result of the pressure exerted by the body on the surface where the individual is and has a great impact on the quality of life by promoting pain and interfering with the performance of the patient's motor functions. Objective: To carry out an integrative review on continuous monitoring of interface pressure and temperature in pressure injury prevention. Methods: The review was carried out in March 2022 in four databases: LILACS, BDENF, MEDLINE, CINAHL and SCOPUS. The following descriptors were used: interface pressure, temperature, pressure ulcer and monitoring. Results: Nine articles were used, most of which were published in the years 2019 and 2021, in several countries, with healthy participants, patients hospitalized in Intensive Care Units at high risk of developing pressure injuries and patients with pressure injuries. As for monitoring, in addition to interface pressure and temperature, humidity and oxygen saturation stand out, at time intervals from 30 minutes to 2 months. The devices used were sensors attached directly to the skin, fibers, pillows, rug, mattress cover or mattresses. Continuous monitoring in the prevention of pressure ulcer is recent and this can be explained by the publication date of the articles and the design of the studies. Conclusion: The studies are promising, but they cannot fail to be complementary to current pressure injury prevention protocols, as the development of this injury is multifactorial and other parameters must be analyzed together.